2022
DOI: 10.1002/smll.202206141
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Repairable Silicon Anodes Using a Multifunctional Binder for High‐Performance Lithium‐Ion Batteries

Abstract: A currently commercialized graphitebased anode in LIBs cannot meet the increasing demand for high energy density because of the limited theoretical specific capacity of graphite (372 mAh g −1 ). [2] As an alternative to the graphite anode for highenergy anode materials, silicon has gained substantial attention due to its high theoretical specific capacity of 3579 mAh g −1 at room temperature (Li 15 Si 4 ), [3] low working potential (0.4 V vs Li + /Li), [4] nontoxicity, and natural abundance. [5] However, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The physical damage of M n + -PODs gels is achieved by self-healing at room temperature when the damaged interface is re-contacted. The M n + -POD healed gels can maintain the damage interface without fracture after stretching to a certain length, which confirms the excellent healing ability of the Si electrode based on the interaction of ionic and hydrogen bonds. , Among M n + -PODs/Si electrodes, the surface cracks of M 2+ -POD-binding Si anodes are significantly less severe than those of M + -PODs/Si electrodes, which makes the coordination effect of divalent ions stronger. The surface of the Ca-POD/Si anode has the least and shallowest cracks because the Ca-POD binder shows an outstanding balance between excellent strength and moderate elasticity, which endow the electrode with small volume fluctuations and displays excellent high-rate capability and superior cycle stability.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The physical damage of M n + -PODs gels is achieved by self-healing at room temperature when the damaged interface is re-contacted. The M n + -POD healed gels can maintain the damage interface without fracture after stretching to a certain length, which confirms the excellent healing ability of the Si electrode based on the interaction of ionic and hydrogen bonds. , Among M n + -PODs/Si electrodes, the surface cracks of M 2+ -POD-binding Si anodes are significantly less severe than those of M + -PODs/Si electrodes, which makes the coordination effect of divalent ions stronger. The surface of the Ca-POD/Si anode has the least and shallowest cracks because the Ca-POD binder shows an outstanding balance between excellent strength and moderate elasticity, which endow the electrode with small volume fluctuations and displays excellent high-rate capability and superior cycle stability.…”
Section: Resultssupporting
confidence: 53%
“…Figures f and S4 show the electrolyte contact angles of M n + -PODs and PAALi binders. The electrolyte contact angle characterizes the electrolyte wettability of the electrode, which is mainly related to the polar groups of the binders. , Due to the similar SD of M n + -PODs, their electrolyte contact angles are relatively close. Figure f shows that the contact angles of M n + -PODs are around 30°, with minor differences within the margin of error.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance battery energy density, multifunctional binder strategies have emerged, aiming to combine diverse benefits from individual polymers. A multifunctional binder refers to a compound used in battery electrode fabrication that serves multiple purposes beyond the traditional role of binding active materials and additives. For instance, binders can also be used to form protective layers, which helps in mitigating side reactions between electrodes and electrolytes to improve battery performance.…”
Section: Types Of Bindersmentioning
confidence: 99%
“…It is worth noting that the dissipation of mechanical stress is crucial for polymer binders in maintaining electrode integrity; thus, the addition of small, soft components to the rigid polymer framework can play a role in buffering and dissipating the stress. 24 Malik et al 25 reported a self-healing and stretchable multifunctional binder PEDOT:PAA:PA (PDPP), where PAA provides mechanical support as a polymer framework and PEDOT enhances the capacity and rate performance. The PA, PEDOT, and PAA interact with each other through dynamic hydrogen bonding and electrostatics, which further enhances the mechanical properties of Si electrodes.…”
Section: Introductionmentioning
confidence: 99%